2006
DOI: 10.1517/13543784.15.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the endocannabinoid system in treating brain disorders

Abstract: Recent cannabinoid research has a primary focus on developing therapeutics against human diseases. Many studies on cannabinoids indicate important progress for protection against several neurodegenerative disorders. Agonists of cannabinoid receptors activate signalling pathways in the brain that are linked to neuronal repair and cell maintenance, and endogenous ligands can also activate neuroprotective responses. These endocannabinoids are bioactive fatty acid amides and esters that are synthesised in the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 125 publications
2
48
0
1
Order By: Relevance
“…Note that although FAAH knockout mice were found to exhibit susceptibility to spastic and proconvulsant activity (Cravatt et al, 2001;Clement et al, 2003), dosing with the potent AM374 compound facilitated a controlled modulation of FAAH to promote protective cannabinergic signals. In relation to the present results, inhibiting endocannabinoid transport has been shown to reduce motor hyperactivity and seizure severity (Lastres-Becker et al, 2002;Marsicano et al, 2003), and several types of neuroprotection have been described with agonists that activate CB1 responses (see Bahr et al, 2006). When endocannabinoid signaling is disrupted through genetic or pharmacological means, the resultant proconvulsant conditions can lead to neuronal compromise (Wallace et al, 2002(Wallace et al, , 2003Marsicano et al, 2003;Monory et al, 2006).…”
Section: Discussionsupporting
confidence: 69%
“…Note that although FAAH knockout mice were found to exhibit susceptibility to spastic and proconvulsant activity (Cravatt et al, 2001;Clement et al, 2003), dosing with the potent AM374 compound facilitated a controlled modulation of FAAH to promote protective cannabinergic signals. In relation to the present results, inhibiting endocannabinoid transport has been shown to reduce motor hyperactivity and seizure severity (Lastres-Becker et al, 2002;Marsicano et al, 2003), and several types of neuroprotection have been described with agonists that activate CB1 responses (see Bahr et al, 2006). When endocannabinoid signaling is disrupted through genetic or pharmacological means, the resultant proconvulsant conditions can lead to neuronal compromise (Wallace et al, 2002(Wallace et al, , 2003Marsicano et al, 2003;Monory et al, 2006).…”
Section: Discussionsupporting
confidence: 69%
“…AM6701 afforded greater protection against the excitotoxic events than AM6702, an inhibitor more potent toward FAAH than MAGL. Blocking endocannabinoid deactivation mechanisms represents an exploitable avenue for reducing excitotoxic damage through dual targeting of pharmacotherapeutic pathways [13,[45][46][47][48]. Blocking the inactivation of endocannabinoid responses is 1 such strategy to promote protective signaling after pathological injury and ameliorate cellular disturbances associated with excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…CB1 receptor activation by endocannabinoids is important for cell viability, and disruption of such signals has been found to prevent neuronal maintenance and to increase excitotoxic vulnerability [45]. A propensity for the receptor activation may be part of repair responses as previous studies have demonstrated elevated endocannabinoid levels in the brain of animals injected with an excitotoxin [14,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research thus far has focused on the protective role of cannabinoids in the central nervous system in response to chronic neurodegenerative diseases, including Alzheimer's disease and multiple sclerosis, or injury associated with stroke or brain trauma (reviewed by Bahr et al, 2006). The exact mechanisms involved in their neuroprotectant effects remain unclear but involve both CB 1 receptor-independent (antioxidant) and -dependent mechanisms (inhibition of Ca 2ϩ influx, reduced glutamate release and excitotoxicity, vasodilatation, increased NGF production and neurotrophic support, and hypothermia).…”
Section: Discussionmentioning
confidence: 99%